Effectiveness of brief intervention and contact for suicide attempters: a randomized controlled trial in five countries - Alexandra Fleischmann; José M Bertolote; Danuta Wasserman; Diego De Leo; Jafar Bolhari; Neury J Botega; Damani De Silva; Michael Phillips; Lakshmi Vijayakumar; Airi Värnik; Lourens Schlebusch; Huong Tran Thi Thanh (Bulletin of the World Health Organization, 2008)
OBJECTIVE: To determine whether brief intervention and contact is effective in reducing subsequent suicide mortality among suicide attempters in low and middle-income countries. METHODS: Suicide attempters (n = 1867) identified by medical staff in the emergency units of eight collaborating hospitals in five culturally different sites (Campinas, Brazil; Chennai, India; Colombo, Sri Lanka; Karaj, Islamic Republic of Iran; and Yuncheng, China) participated, from January 2002 to October 2005, in a randomized controlled trial to receive either treatment as usual, or treatment as usual plus brief intervention and contact (BIC), which included patient education and follow-up. Overall, 91% completed the study. The primary study outcome measurement was death from suicide at 18-month follow-up. FINDINGS: Significantly fewer deaths from suicide occurred in the BIC than in the treatment-as-usual group (0.2% versus 2.2%, respectively; χ2 = 13.83, P < 0.001). CONCLUSION: This low-cost brief intervention may be an important part of suicide prevention programmes for underresourced low- and middle-income countries.